Crecimiento de Barkeria lindleyana (Orchidaceae) en un hábitat suburbano de Costa Rica - Valverde Rojas, Idannia (2015)
By means of sampling techniques applied on 15 plots (20 x 20 m) located in San Juan de Dios, a suburban town of Costa Rica, some conditions of the habitat related to the establishment of Barkeria lindleyana (Orchidaceae) on host plants of small gardens and farms were studied. Two variables were analysed: light intensity and location on the branches. The results indicate that B. lindleyana has the capability to establish itself under different light intensities; however, the results of location test show the average number of orchids found at the distal end of the host branches (where the light intensity is higher) is significantly higher than the averages in middle and basal positions of the branches. Moreover, the most robust and healthy plants were observed in high light conditions. This result, combined to the morphological adaptations B. lindleyana shows, indicates that this species is one of the so-called branchy orchids.